DC-DC boost converter with PWM controller [electronic resource] - Muhammad Syafiq Hamid, author; Mohd. Zaki Daud, supervisor (2011)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2011